2023
DOI: 10.1021/acs.orglett.2c04261
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Regioselective Remote C–H Bond Chalcogenation of Aromatic Amine Derivatives without Using Any Large Template

Abstract: A mild and convenient strategy has been developed for the para-selective chalcogenation of anilide scaffolds via C–H bond functionalization. This methodology employs one of the most earth-abundant and inexpensive Cu(II) catalysts and a commercially available simple aryl chalcogen source without any complex directing template, exogenous ligand, acid/base, oxidant, or other additives. The key feature of this methodology is an impressive regioselectivity along with a wide range of functional group tolerance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the basis of above experimental evidence and related literature, [11,[14][15][16] plausible reaction mechanisms of these selenylation processes are proposed in Scheme 4. Initially, copper (II) readily formed weak ligands with substrate A, [11] which promoted one-electron oxidation of the anilides A by Cu(II), resulting in the formation of N-phenyl acetamide radical B and Cu(I). [15,16] Afterwards, Cu(I) underwent oxidization by diphenyl diselenide to from PhSe * and regenerate Cu(II).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the basis of above experimental evidence and related literature, [11,[14][15][16] plausible reaction mechanisms of these selenylation processes are proposed in Scheme 4. Initially, copper (II) readily formed weak ligands with substrate A, [11] which promoted one-electron oxidation of the anilides A by Cu(II), resulting in the formation of N-phenyl acetamide radical B and Cu(I). [15,16] Afterwards, Cu(I) underwent oxidization by diphenyl diselenide to from PhSe * and regenerate Cu(II).…”
Section: Resultsmentioning
confidence: 94%
“…Recently, during the preparation of this article, Chatterjee et al have reported the para-selective selenylation of CÀ H bonds in benzoyl aromatic amines under copper-catalyzed aerobic reaction conditions (Scheme 1d, up). [11] Coincidentally, we have also achieved selectivity for para-selenylation in this work, although we initially studied ortho-site selenylation reactions.…”
Section: Introductionmentioning
confidence: 95%
“…Given that N ‐sulfenylanilides 1 a and 1 y , which were derived from crossover between the starting materials 1 c and 1 h , were not observed, the transfer of the sulfenyl group likely proceeds in an intermolecular manner. It should be noted that the reaction of anilide 3 a and disulfide 4 a under the standard conditions did not yield 2 a (Scheme 5c), eliminating the possibility that this transformation proceed through intermolecular reaction between anilide 3 and disulfide 4 [14k] …”
Section: Resultsmentioning
confidence: 99%